CELLS INVOLVED IN THE IMMUNE RESPONSE : IV. THE RESPONSE OF NORMAL AND IMMUNE RABBIT BONE MARROW AND LYMPHOID TISSUE LYMPHOCYTES TO ANTIGENS IN VITRO - Singhal, Sharwan K. (The Rockefeller University Press, 1968)
Cell suspensions of immune rabbit lymph nodes and spleen were capable of undergoing blastogenesis and mitosis and of incorporating tritiated thymidine when maintained in culture with the specific antigen in vitro. They did not respond to other, non-cross-reacting antigens. The blastogenic response obtained with immune lymph node cells could be correlated with the antibody synthesizing capacity of fragment cultures prepared from the same lymph nodes. Cell suspensions of immune bone marrow responded to non-cross-reacting antigens only whereas cell suspensions of immune thymus, sacculus rotundus, and appendix did not respond when exposed to any of the antigens tested. On the other hand, neither fragments nor cell suspensions prepared from lymph nodes, spleen, and thymus of normal, unimmunized rabbits responded with antibody formation and blastogenesis when exposed to any of the antigens. However, normal bone marrow cells responded with marked blastogenesis and tritiated thymidine uptake. The specificity of this in vitro bone marrow response was demonstrated by the fact that the injection of a protein antigen in vivo resulted in the loss of reactivity by the marrow cell to that particular antigen but not to the other, non-cross-reacting antigens. Furthermore, bone marrow cells of tolerant rabbits failed to respond to the specific antigen in vitro. It was also demonstrated that normal bone marrow cells incubated with antigen are capable of forming antibody which could be detected by the fluorescent antibody technique. This response of the bone marrow cells has been localized to the lymphocyte-rich fraction of the bone marrow. It is concluded that the bone marrow lymphocyte, by virtue of its capacity to react with blastogenesis and mitosis and with antibody formation upon initial exposure to the antigen, a capacity not possessed by lymphocytes of the other lymphoid organs, has a preeminent role in the sequence of cellular events culminating in antibody formation.